Kultur Sekolah dalam Penguatan Nilai Toleransi pada Sekolah Menengah Atas di Kota Yogyakarta - Ningsih, Indra Rahayu (IJTIMAIYA: Journal of Social Science and Teaching, 2024)
The value of tolerance is a value that must be fulfilled in every school through strengthening school culture. But not every school has a good culture in developing the value of tolerance. The aim of this research is to find out the utilization of school culture in the application of tolerance value. The research used a descriptive qualitative approach. The result of this research shows that the school culture strengthens the value of tolerance through 1) vision-mission has the direction of tolerance value formation. 2) The principal has a strategic role in implementing policies to foster the value of tolerance. 3) Internalization of tolerance in learning by teachers. 4) Tolerance practices in extracurricular activities. It should be realized that attitude formation must be carried out continuously for a long time. At least schools in Yogyakarta provide hope for the realization of the value of tolerance naturally.